Economic Integration of North American Countries: Challenges and Development Prospects - Varlamova Mariia L.; Kushko Zoriana I. (Bìznes Inform, 2025)
The article examines the process of economic integration of North American countries based on the new USMCA agreement, which emerged in response to the challenges of globalization and the transformation of global trade networks. Special attention is given to the stages of transition from the North American Free Trade Agreement (NAFTA) to USMCA, discussing the social, environmental, and technological aspects that are important for shaping new rules of economic interaction. The article underlines that the new agreement regulates minimum wages, environmental requirements, and the protection of intellectual property rights, ensuring more inclusive and balanced economic integration for the participating countries. The analysis of trade volume dynamics since the signing of USMCA concludes that exports and imports of goods between the USA, Canada, and Mexico demonstrate steady growth, indicating the depth of economic interaction. The data shows a simplification of customs control, harmonization of technical standards, and strengthening of supply chains between countries. However, issues such as the worsening trade balance of the United States require a serious review of foreign trade strategies and active support for export potential. The research also demonstrates that foreign direct investment in North America has increased after the implementation of USMCA, indicating a positive impact of the agreement on the region’s attractiveness for foreign investors. This increase in investment emphasizes the importance of integration associations for stable economic development and strengthening the economic competitiveness of participating countries. It is further substantiated that the integration processes in North America, particularly through the USMCA, are essential for sustainable development and adaptation to new global challenges. Recommendations focus on the need for flexibility in agreements, which will allow preserving the balance of interests of all participating countries, ensuring benefits for all participants in the integration process.